Pengetahuan lingkungan hidup siswa/i dalam menjaga kebersihan lingkungan Sekolah Menengah Atas Negeri 1 Kota Sorong - Oktofianus Demetouw; Mulyadi Mulyadi; Marlyn N Lekitoo (Cassowary, 2022)
Knowledge of the environment from 204 students (respondents) has an average score of 249 with an interval scale of 225 - 300 and category 3 of the average score of the questionnaire statement on understanding is 26 and requirements of 223. The level of student knowledge It was concluded descriptively that the environmental knowledge of the students of SMA Negeri 1 Sorong City was high. That of the 204 students as many as 168 (82%) have a total score of 43,097 which the average score is on an interval scale of 225 - 300 with a high category (3) and as many as 36 (18%) have a total score of of 7,667 which the average score is on the interval scale 150 - 225 in the medium category (2). A high level of knowledge can be translated by gender for the entire sample studied. Based on table 5.3. the environmental knowledge of male respondents as many as 93 students has a score of 23,014 with an average score of 247 and female as many as 111 students have a score of 27,751 on environmental knowledge with an average score of 247. Both scores gender if the average score is 249 so that it meets category 3.